2011
DOI: 10.1002/joc.2109
|View full text |Cite
|
Sign up to set email alerts
|

Application of simple clustering on space‐time mapping of mean monthly rainfall pattern

Abstract: Rain gauges in many watersheds are not enough to represent the spatial and temporal variations of precipitation. Many agricultural activities can be highly sensitive to these variations and therefore different monthly or annual precipitation statistics have been widely used in the literature for agricultural planning and management. For example, mean monthly rainfall has been used as one of the main criteria for classifying suitable regions for dryland farming. In this paper, a method for space-time estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Various methods have been employed to overcome these problems. Among them, clustering methods attain more accuracy in estimation by taking into account data similarities (Abedini et al 2008;Nasseri and Zahraie 2010). Research indicated that clustering methods reduce estimation error variance and mean square error and thus improve the accuracy of results for estimating spatial and spatiotemporal patterns of precipitations (Abedini et al 2008;Nasseri and Zahraie 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various methods have been employed to overcome these problems. Among them, clustering methods attain more accuracy in estimation by taking into account data similarities (Abedini et al 2008;Nasseri and Zahraie 2010). Research indicated that clustering methods reduce estimation error variance and mean square error and thus improve the accuracy of results for estimating spatial and spatiotemporal patterns of precipitations (Abedini et al 2008;Nasseri and Zahraie 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Among them, clustering methods attain more accuracy in estimation by taking into account data similarities (Abedini et al 2008;Nasseri and Zahraie 2010). Research indicated that clustering methods reduce estimation error variance and mean square error and thus improve the accuracy of results for estimating spatial and spatiotemporal patterns of precipitations (Abedini et al 2008;Nasseri and Zahraie 2010). Abedini et al (2008) coupled accelerated exact k-mean with the OK method to improve the accuracy of the OK method by clustering piezometric head patterns in west Texas (USA).…”
Section: Introductionmentioning
confidence: 98%
“…To address such challenges in these areas, the literature accentuates the importance of adopting more water-saving technologies through the efficient storage and use of water [11]. Several studies described STRV on different scales [12][13][14][15][16]; however, these studies rarely demonstrated the potential relationship between STRV and yield variability among farmer fields located within the same agricultural watershed. Rainfall studies in the forms of trend analyses and spatial variability over large areas are numerous, but these studies have limited connections to local agricultural challenges.…”
Section: Introductionmentioning
confidence: 99%
“…have been widely used to identify the homogenous regions. Some specific applications of cluster methods include the identification of homogeneous regions for regional flood frequency analysis (Burn, 1989;Burn and Goel 2000;Lecce, 2000;Thandaveswara and Sajikumar, 2000), defining of the homogeneous precipitation regions (Smithers and Schulze, 2001;Nasseri and Zahraie, 2011). Data sets are separated into subregions with similar characteristics by clustering analysis and more sensitive estimation models are set up for these sub-regions.…”
mentioning
confidence: 99%